PENGARUH PENERAPAN GOOD GOVERNANCE DAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Abram Setiafa, 0935030503 (Students Journal of Accounting and Banking, 2013)
This study examined the effect of the application of good governance and the rule of accounting standards towards the quality of local government financial reports. In accordance with the theory that good governance is a guideline in the management of state or local government accounting standards and is one of the basic law in governance, then the required evidence of accountability and implementation of policy guidelines that one through the quality of the governments financial statements.This research used purposive sampling method and obtained a sample of 69 respondents. The data of these studies tested the instrument with validity and reliability and also tested the normality test, and heteroscedasticity, multicolinearity to determine whether there is violation of the classical assumptions. Further analysis, the researcher used multiple regression to explain the relationship between variables. The regression analysis explained that good governance and no significant negative effect on the quality of local government financial statements, governmental accounting standards while positive and significant impact on the quality of local government financial reports.This study has limitations that sampling time is relatively short, yet considering the other major variables that can affect the quality of local government financial reports. Therefore, in future studies are advised to consider other variables as well as the main study period needs to be longer so that it can be generalized.Keywords: Good Governance, Government Accounting Standards, Financial Statement Quality